miR-429 suppresses cell growth and induces apoptosis of human thyroid cancer cell by targeting ZEB1 - Guochang Wu; Haitao Zheng; Jie Xu; Yawen Guo; Guibin Zheng; Ci Ma; Shaolong Hao; Xincheng Liu; Huanjie Chen; Shujian Wei; Xicheng Song; Xiaojie Wang (Artificial Cells, Nanomedicine, and Biotechnology)
Thyroid cancer is now the most common endocrine malignancy and the effect of miR-429 in the development of thyroid cancer still need to be further investigated. The expression level of miR-429 was quantified by qPCR in both clinical samples and cultured cell lines. MTT, flow cytometry, migration analyses and Matrigel invasion assays were conducted to test the proliferation, apoptosis, migration and invasion of MiR-429 transfection in thyroid cancer cell lines. Luciferase activity assay and western blot were conducted to detect the direct effect of miR-429 on Zinc finger E-box-binding homeobox 1 (ZEB1) expression. In this study, it was found that miR-429 was frequently decreased in thyroid cancer tissues and cell lines. Transfection of miR-429 in thyroid cancer cell lines substantially suppressed cell proliferation, migration and invasion. Besides, miR-429 up-regulation would induce apoptosis in different cell lines. ZEB1 was identified as a direct target of miR-429 and miR-429 transfection could inhibit ZEB1 by direct binding to its 3’-untranslated region (3’-UTR). In conclusion, these data indicated that miR-429 could act as a tumour suppressor miRNA and contribute to the development and progression and metastasis of thyroid cancer.